Are fibres in molecular cloud filaments real objects? - Zamora-Avilés, Manuel; Ballesteros-Paredes, Javier; Hartmann, Lee (Monthly notices of the Royal Astronomical Society, 2017)
Abstract. We analyse the morphology and kinematics of dense filamentary structures produced in a numerical simulation of a star-forming cloud of 1.4 × 104 M⊙ e
Gesehen am 22.08.2018